2016
DOI: 10.1038/nnano.2016.196
|View full text |Cite
|
Sign up to set email alerts
|

Microsupercapacitors as miniaturized energy-storage components for on-chip electronics

Abstract: The push towards miniaturized electronics calls for the development of miniaturized energy-storage components that can enable sustained, autonomous operation of electronic devices for applications such as wearable gadgets and wireless sensor networks. Microsupercapacitors have been targeted as a viable route for this purpose, because, though storing less energy than microbatteries, they can be charged and discharged much more rapidly and have an almost unlimited lifetime. In this Review, we discuss the progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
609
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 854 publications
(616 citation statements)
references
References 105 publications
6
609
0
1
Order By: Relevance
“…Micro-supercapacitors are designed with thin-film electrodes assembled in various configurations, 6 typically at the scale of mm 2 or cm 2 footprint area, with the goal of complementing or replacing microbatteries in applications that include power sensors and microelectronic devices. In many such applications, area-normalized capacitance (F cm −2 ), energy, and power (based on the footprint of the device) are the most important performance metrics.…”
Section: Future Needs and Prospectsmentioning
confidence: 99%
“…Micro-supercapacitors are designed with thin-film electrodes assembled in various configurations, 6 typically at the scale of mm 2 or cm 2 footprint area, with the goal of complementing or replacing microbatteries in applications that include power sensors and microelectronic devices. In many such applications, area-normalized capacitance (F cm −2 ), energy, and power (based on the footprint of the device) are the most important performance metrics.…”
Section: Future Needs and Prospectsmentioning
confidence: 99%
“…This adaptive storage building block can be integrated on silicon and combined to miniaturized microsupercapacitors [6] to provide a compact module. With this module coupled to an energy-harvesting source, it could be envisioned for a wireless sensor node to become fully battery-free.…”
Section: Discussionmentioning
confidence: 99%
“…[16] Even at a fast scan rate of 100 mV s −1 , the CV remains nearly rectangular in shape, indicating the high-power capability of printed planar supercapacitors. [3,9] According to the Equation (2) [14,15] Adv. Recently, it has been shown that the areal capacitance gives a more accurate picture of the true performance of a planar supercapacitor compared with gravimetric values.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%